1998
DOI: 10.1007/s004390050813
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and mutational analysis of the human B17 subunit of the mitochondrial respiratory chain complex I

Abstract: Bovine NADH:ubiquinone oxidoreductase (complex 1) of the mitochondrial respiratory chain consists of about 36 nuclear-encoded subunits. We review the current knowledge of the 15 human complex I subunits cloned so far, and report the 598-bp cDNA sequence, the chromosomal localization and the tissue expression of an additional subunit, the B17 subunit. The cDNA open reading frame of B17 comprises 387 bp and encodes a protein of 128 amino acids (calculated Mr 15.5 kDa). There is 82.7% and 78.1% homology, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…While this ignores potential "hot-spots" for mutation in the residual complex I genes as well as the promoter region, we feel that this is sufficiently convincing to contend that complex I is probably not involved in the clinical phenotypes of the patients in this study and perhaps not a cause of myopathic disease in general. This assertion is supported by other recent studies which failed to identify mutations within the NDUFA1 gene in 17 myopathy patients [14] or the NDUFB6 gene in 20 complex I deficient patients [13]. A slight caveat to this conclusion is that although our study utilised high fidelity sequencing as the mutation screening procedure, non-transcribed or unstable mutant mRNAs may have been missed.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While this ignores potential "hot-spots" for mutation in the residual complex I genes as well as the promoter region, we feel that this is sufficiently convincing to contend that complex I is probably not involved in the clinical phenotypes of the patients in this study and perhaps not a cause of myopathic disease in general. This assertion is supported by other recent studies which failed to identify mutations within the NDUFA1 gene in 17 myopathy patients [14] or the NDUFB6 gene in 20 complex I deficient patients [13]. A slight caveat to this conclusion is that although our study utilised high fidelity sequencing as the mutation screening procedure, non-transcribed or unstable mutant mRNAs may have been missed.…”
Section: Discussionsupporting
confidence: 81%
“…This has also been the case with successfully identified pathogenic mutations in complex I nuclear genes [9−12] as well as in unsuccessful studies [13,14]. The multi-subunit nature of enzymes in the mitochondrial respiratory chain imposes a considerable problem in this regard.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Genes of particular interest in this group are the NADH dehydrogenase 1beta 17 kDa (NDUFB6) and protease serine 15 (PRSS15). NDFUB6 belongs to the first enzyme complex of the mitochondrial respiratory chain and has been found to be highly expressed in normal tissues with a high energy demand, such as kidney and heart (Smeitink et al, 1998). PRSS15 is a multifunctional protein widely preserved throughout species from yeast to mammals (Lu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because the ATP levels have been found to be decreased in OVA/ OVA/A.CON and the expression of 17-kDa subunit of complex I is related with energy demand (28), IHC was performed for this subunit. We found that this subunit expressed exclusively in the bronchial epithelium of N.CON mice, whereas it was significantly decreased in OVA/OVA/A.CON mice.…”
Section: Il-4 Mab and Dex Restored The Reduction In Expression Of 17-mentioning
confidence: 99%